Prior oral contraceptive use in ovarian cancer patients: assessing associations with overall and progression-free survival. Issue 1 (December 2015) - Jatoi, Aminah; Foster, Nathan; Kalli, Kimberly; Vierkant, Robert; Zhang, Zhiying; Larson, Melissa; Fridley, Brooke; Goode, Ellen
Abstract Background Prior studies have described a reduced risk of developing ovarian cancer with the use of oral contraceptives. In this context, we decided to examine if oral contraceptive use prior to a diagnosis of ovarian cancer is associated with better overall and progression-free survival. Methods This retrospective cohort study included ovarian cancer patients who were seen at the Mayo Clinic in Rochester, Minnesota from 2000 through 2013. Patients completed a risk factor questionnaire about previous oral contraceptive use, and clinical data were extracted from the electronic medical record. Results A total of 1398 ovarian cancer patients responded to questions on oral contraceptive use; 571 reported no prior use with all others having responded affirmatively to oral contraceptive use. Univariate analyses found that oral contraceptive use (for example, ever versus never) was associated with better overall survival (hazard ratio (HR) 0.73 (95 % confidence interval (CI): 0.62, 0.86); p = 0.0002) and better progression-free survival (HR 0.71 (95 % CI: 0.61, 0.83); p < 0.0001). In multivariate analyses, contraceptive use continued to yield a favorable, statistically significant association with progression-free survival, but such was not the case with overall survival. Conclusions This study suggests that previous oral contraceptive use is associated with improved progression-free survival in patients diagnosed with ovarian cancer.